Determine the coordination of Al and Si of Fe-rich fly ash: The challenge in NMR and how we probe its heterogeneity using X-ray spectromicroscopy. (November 2022) - Li, Jiaqi; Xu, Ke; Geng, Guoqing; Mason, Harris E.
Abstract: Scanning transmission X-ray microscopy (STXM) coupled with ptychographic imaging at Al and Si K-edge is a new probe to the microscale chemistry of heterogenous materials. Here, the combined techniques are applied to study local coordination environment of Fe-rich fly ash (FA). Ptychographic imaging at Al K- and Si K-edge highlights the fine Al- and Si-rich morphological features, respectively, at 6 nm pixel resolution. STXM visualizes the inter- and intra-particle variations in the silicate polymerization degree and two types of Al coordination environment in FA. The Si K-edge of SiO4 connected with four-fold coordinated Al is higher than SiO4 sharing oxygen with six-fold coordinated Al. The result is consistent with bulk nuclear magnetic resonance spectroscopy measurement of the Fe-rich sample which, however, is sensitive to paramagnetic Fe and time-consuming. We demonstrate that the combined method has great potential in the studies of chemically heterogenous aluminosilicates.